Cytotoxic Activity Test Of Ethanolic Extract Of Berenuk Fruit (Crescentia Cujete L.) On Artemia Salina Leach Shrimp Larva Using Brine Shrimp Lethality Test (BSLT) Method - Dona Suzana; Isnani Handayanti (Fakultas Kedokteran Universitas Sriwijaya, 2023)
Introduction. Cancer is one of the leading causes of human death in the world. One of the therapies given to cancer patients is chemotherapy which has cytotoxic effects. One of the plants that have the same effect is the berenuk or calabash (Crescentia cujete L.) plant, from the family of Bignoniaceae, which grows wild and is often referred to as a poisonous plant. However, some people traditionally use this plant as a medicinal plant such as for antifungal, anthelmintic, analgesic, and anti-inflammatory. This plant contains naphthoquinones as one of the cytotoxic chemical compounds and another metabolite secondary such as alkaloids, flavonoids, saponins, tannins, terpenoids, and anthraquinones. Methods. The BSLT (Brine Shrimp Lethality Test) method was used for this study. The powder of berenuk fruit flesh was extracted using ethanol. The obtained solvent was evaporated using a rotary evaporator to obtain a thick extract. The extract was tested on A. salina larva that has been prepared and the value of mortality was observed. Results. The result of the cytotoxic activity test of ethanolic extract of berenuk fruit on A. salina larva had the LC50 value of 529.386 ppm which is categorized as toxic. Conclusion. Extract ethanolic of berenuk fruit on A. salina had cytotoxic activity.